Measuring employee engagement of low-income workers either working at or visiting Marabastad Mall in the City of Tshwane Metropolitan Municipality - Molefe Jonathan Maleka; Cecile Schultz; Lize van Hoek; Leigh-Anne Paul Dachapalli; Suzette Ragadu (Journal of Economics and Behavioral Studies, 2017)
The purpose of this study is to measure employee engagement of low-income workers either working at or visiting Marabastad Mall in the City of Tshwane Metropolitan Municipality (CTMM). The literature review revealed that in the South African context there is a dearth of research on predictors of employee engagement. The research design was a survey and the sample size was six hundred and forty-nine (n=649). The descriptive statistics show that the respondents were moderately disengaged, disaffected, and committed. The descriptive statistics also revealed that respondents moderately disagreed that they had training opportunities and they had a good quality of work life. The inferential statistics showed that males were more engaged than their female counterparts, part-time employees were slightly more engaged than full-time employees and employees who were unionised were more engaged than the non-union members.  It was also found that job satisfaction was the highest predictor of employee engagement (Î² = 0.28, p<0.05). The study has implications for policymakers that employees earning between R1 000.00 and R10 000.00 are less engaged and committed and their job satisfaction levels were low. The implication for managers is that they must be aware that development and recognition of employees and job satisfaction predict employee engagement. Quality of work life and labour relations did not predict employee engagement